Characterization of growth hormone releasing hormone (GHRH) partial gene in buffalo - J, Rajamurugan; Kumar, Subodh; Pandey, O P; Deb, S M; Mitra, Abhijit; Sharma, Arjava (The Indian Journal of Animal Sciences, 2007)
A fragment of 453 bp corresponding to exon 2 and 3 of growth hormone releasing hormone (GHRH) gene was amplified in 60 buffaloes (Bubalus bubalis) of Murrah breed. The HaeIII PCR-RFLP analysis showed the absence of mutant allele and hence monomorphism in the buffalo population studied. Sequence homology indicated that the buffalo GHRH was closest to that of yak with 96.2% similarity, then followed by cattle (95.8%), horse (86.4%), pig (72%), dog (48.5%), rat (32.1%) and mouse (29.4%). The amino acid homology between buffalo and cattle was 100% despite some nucleotide changes. The sequence of the amplicon, which was the first report on buffalo GHRH, was submitted to GenBank.